A study of preoperative predictive factors of strangulation in acute small intestinal obstruction - Nandyala, Venkat Narsimha Reddy; Chintakindi, Santhosh Babu; Kundarapu, Gopikanth (International Surgery Journal, 2016)
Background:Acute small intestinal obstruction is a common surgical emergency where outcomes are often influenced by the presence of strangulation. Identification of criteria which can predict strangulation among patients presenting with acute small intestinal obstruction can help in early decision making regarding management and thereby can ensure better outcomes. A prospective observational study was carried out among 54 patients presenting with acute small intestinal obstruction to document clinically the signs and symptoms which can predict strangulation early along with laboratory parameters and findings on imaging using ultrasound and color doppler. Methods: A delayed presentation beyond 72 hours with bleeding per rectum and fever along with marked tachycardia with hypotension were the significant criteria observed among patients with strangulated obstruction. Results:On laboratory evaluation, leukocytosis with an elevated serum lactate was significant in strangulated obstruction whereas on imaging ultrasound abdomen supplemented with a color doppler proved to be an investigation of choice in predicting strangulation. Conclusions:A combination of clinical, laboratory and imaging criteria can be useful in predicting strangulation among patients presenting with acute small intestinal obstruction thereby ensuring an early surgical intervention and better outcomes.